Argumentation and Critical Thinking Skills with Argument-Driven Inquiry (ADI) Learning Model: A Literature Review - Limbong, Stella Afrilita; Dasna, I Wayan; Munzil, Munzil (Universitas Negeri Malang, 2023)
The development of globalization affects all aspects of life, including education. The world of education entering the fifth revolution is characterized by the use of digital devices and the internet in learning. This results in demands and responsibilities for teachers and students to train the framework of creativity, communication, collaboration, and critical thinking known as 4C.One effective way to enhance students' critical thinking and communication skills is through the implementation of the ADI (Argument-Driven Inquiry) learning model.The application of the ADI model is focused on the activities of students in building their knowledge independently to convey the results of their findings as a form of communication. Implementing ADI in chemistry learning will train students to find a finding based on scientific evidence. However, implementing the ADI learning model has obstacles to achieving learning objectives. One is that students are less accustomed to arguing during learning. This causes the ADI learning model to need to be assisted by other approach models in order to increase the effectiveness of ADI learning. This literature review applies Systematic Literature Review (SLR) by reviewing the results of previous research and adjusting to the focus of the study. The results of the review of some of these studies indicate that applying the ADI learning model with the help of several approaches, such as metacognitive and practicum-assisted learning chemistry, provides better results in increasing students' critical thinking skills and scientific argumentation.